Exposure monitoring of graphene nanoplatelets manufacturing workplaces. (11th May 2016) - Lee, Ji Hyun; Han, Jong Hun; Kim, Jae Hyun; Kim, Boowook; Bello, Dhimiter; Kim, Jin Kwon; Lee, Gun Ho; Sohn, Eun Kyung; Lee, Kyungmin; Ahn, Kangho; Faustman, Elaine M.; Yu, Il Je
Abstract: Graphenes have emerged as a highly promising, two-dimensional engineered nanomaterial that can possibly substitute carbon nanotubes. They are being explored in numerous R&D and industrial applications in laboratories across the globe, leading to possible human and environmental exposures to them. Yet, there are no published data on graphene exposures in occupational settings and no readily available methods for their detection and quantitation exist. This study investigates for the first time the potential exposure of workers and research personnel to graphenes in two research facilities and evaluates the status of the control measures. One facility manufactures graphene using graphite exfoliation and chemical vapor deposition (CVD), while the other facility grows graphene on a copper plate using CVD, which is then transferred to a polyethylene terephthalate (PET) sheet. Graphene exposures and process emissions were investigated for three tasks – CVD growth, exfoliation, and transfer – using a multi-metric approach, which utilizes several direct reading instruments, integrated sampling, and chemical and morphological analysis. Real-time instruments included a dust monitor, condensation particle counter (CPC), nanoparticle surface area monitor, scanning mobility particle sizer, and an aethalometer. Morphologically, graphenes and other nanostructures released from the work process were investigated using a transmission electron microscope (TEM). Graphenes were quantified in airborne respirable samples as elemental carbon via thermo-optical analysis. The mass concentrations of total suspended particulate at Workplaces A and B were very low, and elemental carbon concentrations were mostly below the detection limit, indicating very low exposure to graphene or any other particles. The real-time monitoring, especially the aethalometer, showed a good response to the released black carbon, providing a signature of the graphene released during the opening of the CVD reactor at Workplace A. The TEM observation of the samples obtained from Workplaces A and B showed graphene-like structures and aggregated/agglomerated carbon structures. Taken together, the current findings on common scenarios (exfoliation, CVD growth, and transfer), while not inclusive of all graphene manufacturing processes, indicate very minimal graphene or particle exposure at facilities manufacturing graphenes with good manufacturing practices.